1998
DOI: 10.1038/sj.jhh.1000655
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene polymorphism in Nepal

Abstract: It has recently been found that there were very few hypertensives in the inhabitants of one Nepalese village, even though their salt consumption, per capita, was as high as citizens in many western countries. To evaluate the genetic factors involved in this phenomenon, we studied whether they had a special genotype distribution of angiotensinconverting enzyme (ACE) gene I/D polymorphism, which was recently reported to be involved in salt sensitivity.One hundred and thirty-eight subjects were evaluated in Nepal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Thus, the frequency differences within the subgroups (although not significant after Bonferroni correction, p  < 0.00250), could be attributed to their evolutionary adaptation. The observed genotypic frequency of ACE I/D in Tamangs was in agreement with frequency distribution reported from inhabitants of Kotyang, majority of whom were Tamangs [30]. Tamangs are indigenous inhabitants of the western Himalayan regions and one of the major Tibeto-Burman speaking communities who trace their ancestry to Tibet and further back to Mongolia ( Tamang people.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the frequency differences within the subgroups (although not significant after Bonferroni correction, p  < 0.00250), could be attributed to their evolutionary adaptation. The observed genotypic frequency of ACE I/D in Tamangs was in agreement with frequency distribution reported from inhabitants of Kotyang, majority of whom were Tamangs [30]. Tamangs are indigenous inhabitants of the western Himalayan regions and one of the major Tibeto-Burman speaking communities who trace their ancestry to Tibet and further back to Mongolia ( Tamang people.…”
Section: Discussionsupporting
confidence: 85%
“…It is, however, difficult to obtain large enough sample size of Sherpas who have lost adaptation to high altitude because of the fact that most Sherpas live at high altitude throughout their lifetime. Thus, we chose a population in Kathmandu who reside geographically near to Namche Bazaar as a reference group principally based on the study by Prugnolle et.al 17 in which the authors demonstrated that geography predicts neutral genetic diversity of human populations and on a investigation 18 in that study the authors demonstrated that ACE I/D polymorphism was distributed continuously in populations in the Asia continent, including Chinese, Japanese, Bangladeshi, Indian, and Sikh, and reportedly Nepalese as well 19 . Therefore, we believe that the comparison of the ACE I/D polymorphism between the two populations in the current study is valid and reliable.…”
Section: Genotypic Distributions and Allelic Frequencies Of The Ace Imentioning
confidence: 99%
“…In addition, specific for the ACE I/D polymorphism, it is distributed continuously in populations in the Asia continent, including Chinese, Japanese, Bangladeshi, Indian, and Sikh 18 , and reportedly Nepalese as well. 19 Thus, the non-Sherpa Nepalese in Kathmandu were chosen as a reference control in comparison with Sherpas in the current comparative genetic study. Except for difference in high-altitude exposure between the two groups, other environmental factors such as nutrition, physical training, and medical health services were felt to be essentially equivalent in the current Sherpa and the non-Sherpa Nepalese groups.…”
Section: Settings and Participantsmentioning
confidence: 99%
“…Only a handful of published genetic studies on Gorkhas/Nepalese are available56789101112. Nepal is situated just to the south of the Himalayan mountain peaks.…”
mentioning
confidence: 99%